Effectiveness of maxillary arch expansion using clear aligners in adult patients: a systematic review and meta-analysis - Kalekar Anjali Anil; Manchanda Jyoti; Chavan Santosh; Bhad Wasundhara A.; Atram Harish; Badu Priyanka; Tarde Priyanka (Sciendo, 2024)
Invisalign, introduced by Align Technology, Inc. in 1997, is a system of clear plastic aligners that provides aesthetic orthodontic treatment plus treatment customisation. Created using impressions or intraoral digital scans, patients wear and sequentially exchange removable, 0.75 mm thick polyurethane appliances. The aligners improve smile appearance, correct dentoalveolar posterior crossbites, increase arch length, relieve crowding, and provide more space for tooth alignment. Dentoalveolar expansion is a preferred alternative to interproximal tooth reduction when treating a patient using the Invisalign clear appliance.